Effect of the elderly on household's financial transactions: Evidence from Japan and Korea - Young-Min Kim (Global Business & Finance Review (GBFR), 2022)
Purpose: This study investigates the effect of the elderly on the household's financial transactions in Japan and Korea. Design/methodology/approach: Using financial transactions from Japanese and Korean central banks from 2009 to 2020 on a quarterly basis, this study employ AR (1) for estimation. Financial assets are largely classified into currency, stock, bond, and insurance while the elderly are divided into 60s,70s, and 80s. Findings: The size of those aged over 70 and 80 has a relatively more significant effect on the financial transactions in Japan and Korea. The growth of those aged 60 has a significant effect on the household's financial transactions in Japan while the growth of 80+ has a more significant effect in Korea. The interaction between the size and growth of those in their 60s and 80s+ has the most significant effect on the household's financial transactions in Japan and Korea, respectively. The interaction between the growing elderly population and life expectancy has no effect on the financial transactions in Japan while it has a significant effect in Korea. Research limitations/implications: This study implies that the elderly gives different effect on household's financial transactions. Also, each old age cohort such as 60s, 70s, and 80s has different effect on the transactions. Originality/value: This study proposes that the size and growth of the elderly both gives different effect on risky and non-risky financial transactions.
Keywords: 650; The elderly; household; financial transaction; demography; life expectancy